Turnover Intentions in Pakistani Telecommunication Industries: An Empirical Assessment - Sarwar, Huma (Archives of Business Research, 2017)
Organizational socialization is assumed to be a vitally important influence on job satisfaction, organizational commitment, innovation, cooperation, and ultimately organizational performance. There is a fundamental assumption underlying virtually all existing work on organizational socialization that all newcomers will remain with an organization for some time. The research presented here begins to relax some of the assumptions underlying current models of socialization where the organization and the new recruit are going concerns. Accordingly, this research is trying to investigate the impact of organizational supported socialization tactics on turn over intentions of new comers working in telecommunication industry of Pakistan. Moreover, this report will also examine the mediating role of job embeddedness (on-the-job embeddedness and off-the-job embeddedness) in the relationships of organizational supported socialization tactics and turnover intentions. To explore the study’s objectives, data collected from 300 employees working in five different telecommunication companies of Pakistan. Findings here suggest that workers are quite distinct in how long they expect to stay with a firm, regardless of their explicit labor contract, and that this variance in anticipated tenure does make a difference in the extent to which these newcomers learn and adapt to their organizations, their jobs, and their social environments, and in the outcomes they experience. This research provides clear empirical support that how long newcomers expect to maintain a relationship with their new organizations has a profound impact on their socialization experiences, and explores the nuances of the impact of this anticipated tenure alone and in interaction with other factors on the socialization process and its outcomes.